The relationship between small intestinal bacterial overgrowth and constipation in children – a comprehensive review - Mares, Cristina Roxana; Săsăran, Maria Oana; Mărginean, Cristina Oana (Frontiers in Cellular and Infection Microbiology, 2024)
Small intestinal bacterial overgrowth (SIBO) is characterized by an increase in the bacterial population of the small intestine due to an imbalance between the amount of bacteria and the intestinal barrier. Pediatric SIBO presents with a wide spectrum of symptoms, ranging from mild gastrointestinal complaints to malabsorption or malnutrition. Breath tests are commonly used as noninvasive diagnostic tools for SIBO, but a standardized methodology is currently unavailable. Intestinal flora produces methane which slows intestinal transit and increases the contractile activity of small intestine. Emerging literature suggests a correlation between overgrowth of methanogenic bacteria in the intestines and constipation. Treatment of SIBO involves administration of antibacterial therapy in addition to management of underlying conditions and optimal dietary adjustments. However, research on antibiotic treatment for pediatric patients with constipation and SIBO is limited and has yielded conflicting results. In the current review, we summarize the state-of-the-art of the field and discuss previous treatment attempts and currently used regimens for SIBO patients with constipation, with a focus on pediatric populations.